The greatest hockey records - Doeden, Matt. (Mankato, Minn. : Capstone Press, 2009)
"Short stories and tables of statistics describe the history and greatest records of the National Hockey League"--Provided by publisher.
Includes bibliographical references (p. 31) and index.
"RL: 4; IL: 3-9"--P. [4] of cover.
860
Accelerated Reader AR
Keywords: National Hockey League -- Juvenile literature; Hockey -- Records -- United States -- Juvenile literature; Hockey -- Records -- Canada -- Juvenile literature